Generalized discrete event system specification: a state-of-the-art study. (June 2022) - Zacharewicz, Gregory
The Generalized Discrete Event System specification (G-DEVS) language was introduced by Norbert Giambiasi in the 1990s. This paper first examines the specification of G-DEVS and gives an historical view of N Giambiasi's works that contributed to this concept. The paper particularly focuses on the extension of G-DEVS to distributed simulation. An example of a G-DEVS model of a ski chairlift system with chair and skier is proposed to show the accuracy gained by using G-DEVS instead of other classical discrete event modeling formalisms. Then, the paper presents how G-DEVS has been extended for interoperability with other components in the context of supply chain modeling and simulation coping, with the possibility to compose different model formats at simulation time. Next, the focus is on a G-DEVS editor tool and its extensions: LSIS_DME. The distributed simulation and the high-level architecture standard were used to support the interoperability of various models and simulators.